Desain Meja Kerja dan Pengaturan Komponen Pendukung Live Streaming Online Shop yang Ergonomis untuk Mengurangi Resiko Musculoskeletal Disorders (Studi Kasus PT. XYZ) - Priyono, Lulud Akidin; Hutabarat, Julianus; Septiari, Renny (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This study was conducted at PT. XYZ to evaluate and reduce the risk of musculoskeletal disorders among host streamers through the design of ergonomic workstations. The research method used was a quantitative case study approach, with the population consisting of employees at PT. XYZ who worked as host streamers. Primary data were collected through observation, questionnaires, guidelines, and interviews. Posture measurements were taken using the REBA (Rapid Entire Body Assessment) and RULA (Rapid Upper Limb Assessment) methods. The results indicated that prior to the intervention, host streamers had REBA and RULA scores that signified a high risk of musculoskeletal disorders, particularly in the neck, shoulders, back, and legs. After implementing an adjustable live streaming workstation design, along with adjustments to lighting and microphone positions, there was a significant decrease in the REBA and RULA scores. The REBA score decreased from 10 to 1, and the average RULA score dropped from 7 to 3. This indicated a significant reduction in the risk of musculoskeletal disorders. This indicates a significant reduction in the risk of musculoskeletal disorders. Thus, designing an adjustable ergonomic workbench significantly reduces the risk of musculoskeletal disorders in host streamers at PT XYZ and improves worker comfort.